2013
DOI: 10.1155/2013/493138
|View full text |Cite
|
Sign up to set email alerts
|

Tregitope Peptides: The Active Pharmaceutical Ingredient of IVIG?

Abstract: Five years ago, we reported the identification and characterization of several regulatory T-cell epitopes (now called Tregitopes) that were discovered in the heavy and light chains of IgG (De Groot et al. Blood, 2008). When added ex vivo to human PBMCs, these Tregitopes activated regulatory T cells (Tregs), increased expression of the transcription factor FoxP3, and induced IL-10 expression in CD4+ T cells. We have now shown that coadministration of the Tregitopes in vivo, in a number of different murine model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 46 publications
0
19
0
Order By: Relevance
“…It has been proposed that Tregitopes represent an evolutionary mechanism by which to suppress autoreactivity to the wide array of different immunoglobulin molecules that are created during immune development,107 and may be the mechanism underlying the efficacy of intravenous immunoglobulin in the treatment of IMIDs 108. Tregitopes can ameliorate inflammation in several murine models of autoimmunity, and are in preclinical stages of development for the treatment of IMIDs 107…”
Section: Targeting Specific Cellular Subsetsmentioning
confidence: 99%
“…It has been proposed that Tregitopes represent an evolutionary mechanism by which to suppress autoreactivity to the wide array of different immunoglobulin molecules that are created during immune development,107 and may be the mechanism underlying the efficacy of intravenous immunoglobulin in the treatment of IMIDs 108. Tregitopes can ameliorate inflammation in several murine models of autoimmunity, and are in preclinical stages of development for the treatment of IMIDs 107…”
Section: Targeting Specific Cellular Subsetsmentioning
confidence: 99%
“…Tolerance through regulatory T cell epitopes. The C H 2 domain of the IgG Fc fragment contains atypical T cell epitopes, which during co-presentation of Fc with associated antigen, has been shown to expand antigen-specific CD4 + CD25 high Foxp3 + regulatory T cells (Tregs) [20]. Fc-derived regulatory T cell epitopes, referred to as Tregitopes, were also found to confer tolerance to recombinant adeno-associated virus gene transfer vectors [21].…”
Section: Indeed Fcriib Is the Only Fc Receptor That Is Constitutivementioning
confidence: 99%
“…These Tregitopes protect the FVIIIFc molecules from the deleterious anti-FVIII immune response by inducing the expansion of Tregs. 9 Krishnamoorthy et al showed, in FVIII-deficient mice, a decreased immune response to FVIIIFc products. 10 As this is a fairly newly approved product, we do not have enough clinical data or randomized trials on its use in ITI.…”
Section: Evidence Of Immunogenicity Of Fviii Products Coupled To Humamentioning
confidence: 99%